1859 N.M. Laws 94–96, An Act prohibiting the carrying of Weapons, concealed or other-wise, §§ 1-2. - (:unkn) unknown (General Publisher, 1859)
Prohibited the carry, concealed or openly, of any pistols, Bowie-knives, cuchillo de cinto, arkansas toothpick, Spanish dagger, slung-shot, or any other deadly weapon. Violators fined not less than fifty dollars but no more than one hundred dollars.
--
Keywords: CARRY